Gold a cultural encyclopedia - Venable, Shannon L.; ebrary, Inc. (Santa Barbara, Calif. : ABC-CLIO, 2011)
"This encyclopedia provides detailed information about the historical, cultural, social, religious, economic, and scientific significance of gold, across the globe and throughout history"--
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Gold -- Social aspects -- History -- Encyclopedias; Goldwork -- History -- Encyclopedias; Gold -- Metallurgy -- History -- Encyclopedias; Gold in art -- History -- Encyclopedias; Electronic books